(3JfHjg Gdedhc hGdecGFOs - (3YeQh Hf HMQ Hf eMHhH GdcfGfj HGdhdGA, GddjKj, CHh YKeGf, GdLGMX,J (B255 (3g` s
(3ChdgG (B:s
(3gPG cJGH jTJed Ydi PcQ JfHjg Gdedhc hGdecGFO , djMUd YfO eWGdYJg GdEMJQGR ef cd UOjb hQajb , HOCg HPcQ ecGFO GdaQS , hKfi HecGFO GdQhe s
(3BNQgG (B:s
(3NJeg HecGFO GdYQH s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B74 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B7s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B22 - (3U (B549 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdSjGSI hGdGLJeGYs